Development of self-assessment MOOC model for language course to support students’ learning performance - Hashim, Hasmaini (2021)
This study is to propose a model of effectiveness attributes for self-assessment MOOC in language learning to support students’ learning performance. It assumes that student activities in online learning courses differ based on cognitive style preferences. The methodology is a triangulation of post-test scores, students perception survey, and expert panel opinions. The research framework consists of three phases: analysis, design and development, and evaluation. To determine suitable assessment elements, a meta-analysis was conducted in the analysis phase. Aiming to improve student performance in language learning, a self-assessment MOOC model (SA-MOOC) based on student characteristic dimensions was designed and developed during the second phase. The SA-MOOC model, design, and prototype were validated by related experts during Phase 2. In the evaluation phase, a post-test with unequal post-test control group design was adopted to test the effectiveness of the prototype of the SA-MOOC model. The instruments used in this study are postal tests and perceptions of the SA-MOOC model based on student characteristic dimensions. A total of 306 respondents from a public university were involved in this study. Data were analyzed using descriptive, non-parametric analysis and structural equation modeling with partial smallest squares (PLS-SEM). The results show that there is a strong relationship between language learning skills and student performance (listening, speaking and writing) and there is a positive impact on students' self-efficacy language learning skills (listening, speaking, reading and writing) on improvement of students’ performance. The elemental dimension application of student characteristics results in greater student performance in student scores and self-efficacy skills (listening, speaking, reading and writing). As an implication, the formation of the SA-MOOC model provides guidelines and concept models for developers of MOOCs to assist the assessment design process and to implement assessment design based on student characteristic dimensions. For future studies, the proposed model can be refined for affective performance components and can be further explored for other potential elements of student characteristics to support student performance.